Evaluation of C Reactive Protein in Acute Ischemic Stroke (Bangladesh Journal of Neuroscience, 2014)
Background: Stroke is a dreadful health hazard all over the world as well as in our country. The relationship between serum C-reactive protein (CRP) level and acute ischaemic stroke is not well studied especially in Bangladesh. Aims and Objectives: To evaluate the association of C-reactive protein (CRP) in acute ischemic stroke .Materials and Methods: This case-control study was carried out in the Department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during the period from January 2006 to December 2007. A total of 30 acute ischaemic stroke patients were included in the case group. Another 30 age and sex matched and apparently healthy persons without any stroke were taken as controls. Results: The stroke patients [21 (70.0%) male; mean age, 56.3 (SD±13.7) years] and control subjects [25 (83.3%) male; mean age, 53.4 (SD ± 9.9) years] were similar in age and sex (p>0.05 each). CRP level was significantly higher in acute ischaemic stroke patients than that of control [42.06 (SD ± 21.26) mg/L; vs 4.30 (SD ± 0.072) mg/L; p